Characterization of Au Thin Films on n-type Si for Photovoltaic Applications - Mat Nayan, Nurul Athirah; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2024)
The efficiency and performance of photovoltaic devices is challenges to achieve due to the low electrical contact resistance and poor light absorption characteristic in the devices. In this report, Au thin films was deposited on n-type silicon using DC sputtering technique followed by laser treatment by using Nd:YAG laser at different energy. The sample were characterized based on topological, morphological, electrical, and optical properties by using Atomic Force Microscope (AFM), Scanning Electron Microscope (SEM), Four-Point Probe and UV-Vis Spectrophotometer. The topology analysis by AFM shows the sample with 60 mJ energy has the highest grain size and surface roughness as compared to as-deposited sample. The SEM characterize of morphological properties show the sample with 80 mJ have many defects that appeared on the surface compared to 60 mJ due to highest laser energy applied. The measured result showed the decreased in resistivity, going from 4.34 ×  to 3.06 ×  Ω/cm, for the as-deposited sample and the sample annealed at 60 mJ. The resistivity of sample threated at 60 mJ achieved peak performance which providing valuable insights for the advancement of photovoltaic devices. The optical analysis by UV-Vis shows the sample that annealed with 60 mJ have the highest absorption of light with average 8.6 at a wavelength of 600 nm. The results indicate that the laser annealing could improve the efficiency of Au thin film, which can be potentially applied in photovoltaic devices.